Strange loops: Producing history in financial times - Amin Samman (Finance and Society, 2020)
In this rejoinder, I discuss three fundamental "deadlocks" raised by contributors to this forum. These relate to the status of historical discourse, financial market logics, and above all the figure of the 'strange loop', which I put forward as a means of reorienting historical thought. I also offer some preliminary remarks on why History in Financial Times departs from conventional forms of historicism in political economy, as well as a further set of reflections on the contemporaneity of the book's argumentation.
Keywords: 300